REPRESENTASI IDEOLOGI PATRIARKI DALAM TALK SHOW MATA NAJWA: EMPATI LINGUISTIK SEBAGAI MEKANISME LEGITIMASI PATRIARKI DALAM KONTEKS SOSIAL INDONESIA - Sulistyaningsih, Eny (Universitas Hamzanwadi, 2026)
This study aims to reveal the representation of patriarchal ideology in the Mata Najwa episode Enaknya Jadi Laki-Laki using Sara Mills’ critical discourse analysis model. The scope of the research focuses on two analytic elements, namely subject–object positioning and lexical choices within the speakers’ dialogue. This descriptive qualitative study uses a full transcript of the YouTube episode as its primary data. The analysis shows that men are consistently positioned as agents with authority and freedom, while women appear as objects of moral, domestic, and social evaluation. A key finding of this study is the presence of linguistic empathy that appears protective toward women but ultimately reinforces restrictions and normalizes inequality. Lexical items such as “melindungi”, “kodrat”, and “motherhood penalty” function as ideological tools that maintain gender hierarchy. The study concludes that language in talk shows not only conveys opinion but also reconstructs power relations that privilege men and disadvantage women.